Effects of miR-26a on Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells by a Mesoporous Silica Nanoparticle - PEI - Peptide System - Yan J (Dove Medical Press, 2020)
Jia Yan, Xiaoli Lu, Xinchen Zhu, Xiaokun Hu, Lili Wang, Jun Qian, Feimin Zhang, Mei Liu Jiangsu Key Laboratory of Oral Diseases, Department of Prosthodontics, Affiliated Hospital of Stomatology, Nanjing Medical University, Nanjing 210029, People’s Republic of ChinaCorrespondence: Feimin Zhang; Mei LiuJiangsu Key Laboratory of Oral Diseases, Department of Prosthodontics, Affiliated Hospital of Stomatology, Nanjing Medical University, Nanjing 210029, People’s Republic of ChinaTel +86 25 8503 1831Fax +86 25 8651 6414Email fmzhang@njmu.edu.cn; liumei2017@njmu.edu.cnIntroduction: RNA-based therapy for bone repair and regeneration is a highly safe and effective approach, which has been extensively investigated in recent years. However, the molecular stability of RNA agents still remains insufficient for clinical application. High porosity, tunable size, and ideal biodegradability and biosafety are a few of the characters of mesoporous silicon nanoparticles (MSNs) that render them a promising biomaterial carrier for RNA treatment.Materials and Methods: In this study, a novel miR-26a delivery system was constructed based on MSNs. Next, we assessed the miRNA protection of the delivery vehicles. Then, rat bone marrow mesenchymal stem cells (rBMSCs) were incubated with the vectors, and the transfection efficiency, cellular uptake, and effects on cell viability and osteogenic differentiation were evaluated.Results: The results demonstrated that the vectors protected miR-26a from degradation in vitro and delivered it into the cytoplasm. A relatively low concentration of the delivery systems significantly increased osteogenic differentiation of rBMSCs.Conclusion: The vectors constructed in our study provide new methods and strategies for the delivery of microRNAs in bone tissue engineering.Keywords: nanocarrier, microRNAs, osteoinduction, tissue engineering